CITRAAN DALAM KUMPULAN PUISI SYAHADAT SENGGAMA KARYA ASRO AL MURTHAWY - Sujoko Sujoko; Edy Pranata Nasution (Universitas Batanghari, 2020)
This research is aimed at describing imagery in the poetry collection Syahadat Senggama by Asro Al Murthawy so that readers know that imagery is an important part of poetry. Besides, this research is qualitative descriptive in a form of words or sentences which consist of kinds of imagery in the poetry collection Syahadat Senggama by Asro Al Murthawy. The data of this research is quotations of words or sentences which contain imagery and the source of the data is the poetry collection of Asro Al Murthawy entitled Syahadat Senggama. This poetry collection is the second edition which published in November 2016 and has 60 pages. The technique of collecting the data is read and note-taking technique. Based on the result of the research, it can be concluded that the collection of poetry in Syahadat Senggama Asro Al Murthawy used 7 kinds of imagery, they are; sight, hearing, touch, smell, taste, movement, and thought. From those 7 imageries, the most dominant imagery occured in the poetry is see imagery. While the least dominant is taste and smell imagery.